Resource overlap and dilution effects shape host plant use in a myrmecophilous butterfly. Issue 4 (14th February 2019) - Valdés, Alicia; Ehrlén, Johan
Abstract: The effects of consumers on fitness of resource organisms are a complex function of the spatio‐temporal distribution of the resources, consumer functional responses and trait preferences, and availability of other resources. The ubiquitous variation in the intensity of species interactions has important consequences for the ecological and evolutionary dynamics of natural populations. Nevertheless, little is known about the processes causing this variation and their operational scales. Here, we examine how variation in the intensity of a consumer–resource interaction is related to resource timing, resource density and abundance of other resources. Using the butterfly consumer Phengaris alcon and its two sequential resources, the host plant Gentiana pneumonanthe and the host ants Myrmica spp., we investigated how butterfly egg‐laying depended on focal host plant phenology, density and phenology of neighbouring host plants and host ant abundance. Butterflies preferred plants that simultaneously maximized the availability of both larval resources in time and space, that is, they chose early‐flowering plants that were of higher nutritional quality for larvae where host ants were abundant. Both the probability of oviposition and the number of eggs were lower in plant individuals with a high neighbour density than in more isolated plants, and this dilution effect was stronger when neighbours flowered early. Our results show that plant–herbivore interactions simultaneously depend on the spatio‐temporal distribution of a focal resource and on the small‐scale spatial variation in the abundance of other herbivore resources. Given that consumers have negative effects on fitness and prefer certain timing of the resource organisms, this implies that processes acting at the levels of individuals, populations and communities simultaneously contribute to variation in consumer‐mediated natural selection. Abstract : Plant–herbivore interactions simultaneously depend on the spatio‐temporal distribution of a focal resource and on the small‐scale spatial variation in the abundance of other resources. This shows that variation in consumer‐mediated natural selection can be the outcome of simultaneous and interactive processes acting at the levels of individuals, populations and communities.